Materials nanoarchitectonics at two-dimensional liquid interfaces - Ariga, Katsuhiko; Matsumoto, Michio; Mori, Taizo; Shrestha, Lok Kumar (Beilstein Journal of Nanotechnology, 2019)
Much attention has been paid to the synthesis of low-dimensional materials from small units such as functional molecules. Bottom-up approaches to create new low-dimensional materials with various functional units can be realized with the emerging concept of nanoarchitectonics. In this review article, we overview recent research progresses on materials nanoarchitectonics at two-dimensional liquid interfaces, which are dimensionally restricted media with some freedoms of molecular motion. Specific characteristics of molecular interactions and functions at liquid interfaces are briefly explained in the first parts. The following sections overview several topics on materials nanoarchitectonics at liquid interfaces, such as the preparation of two-dimensional metal-organic frameworks and covalent organic frameworks, and the fabrication of low-dimensional and specifically structured nanocarbons and their assemblies at liquid–liquid interfaces. Finally, interfacial nanoarchitectonics of biomaterials including the regulation of orientation and differentiation of living cells are explained. In the recent examples described in this review, various materials such as molecular machines, molecular receptors, block-copolymer, DNA origami, nanocarbon, phages, and stem cells were assembled at liquid interfaces by using various useful techniques. This review overviews techniques such as conventional Langmuir–Blodgett method, vortex Langmuir–Blodgett method, liquid–liquid interfacial precipitation, instructed assembly, and layer-by-layer assembly to give low-dimensional materials including nanowires, nanowhiskers, nanosheets, cubic objects, molecular patterns, supramolecular polymers, metal-organic frameworks and covalent organic frameworks. The nanoarchitecture materials can be used for various applications such as molecular recognition, sensors, photodetectors, supercapacitors, supramolecular differentiation, enzyme reactors, cell differentiation control, and hemodialysis.
Keywords: film; interface; low-dimensional material; nanoarchitectonics; self-assembly